A fluorescence detection method for peroxynitrite ion and its application

By using carbon quantum dot composite nanomaterials as fluorescence probes, the peroxynitrite ions are detected using fluorescence emission peak movement, which solves the problem of insufficient detection sensitivity and selectivity in the prior art, and achieves efficient and stable detection effects.

CN118533805BActive Publication Date: 2025-02-18SHENZHEN JIAHE XINGYE INFORMATION TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410652004.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-24
Publication Date
2025-02-18
Estimated Expiration
2044-05-24

AI Technical Summary

Technical Problem

The existing peroxynitrite ion fluorescence detection methods have problems such as single-wavelength fluorescence intensity being easily disturbed by environmental and instrument fluctuations, poor water solubility and poor photobleaching resistance of organic fluorescence probes, resulting in insufficient detection sensitivity and selectivity.

Method used

Carbon quantum dot composite nanomaterials were used as fluorescent probes to cause fluorescence emission peaks to move by reacting with peroxynitrite ions. The emission peak displacement value at 495nm of carbon quantum dots was used for detection, and a wavelength-moving detection system was constructed.

Benefits of technology

The detection of peroxynitrite ions is achieved with high sensitivity, good selectivity and good stability, avoiding the impact of environmental and instrument fluctuations on the detection results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118533805B_ABST
    Figure CN118533805B_ABST
Patent Text Reader

Abstract

The present invention discloses a fluorescence detection method of peroxynitrite ion and its application. A method for detecting peroxynitrite ion by a nanocomposite material comprises the following steps: mixing a peroxynitrite ion standard sample with a carbon quantum dot nanocomposite material solution containing fluorescent carbon quantum dots A and fluorescent carbon quantum dots B, exciting, measuring the displacement value of the emission peak at 495nm, and obtaining a linear equation between the peroxynitrite ion concentration and the wavelength shift value; mixing the sample to be tested with the carbon quantum dot nanocomposite material solution, exciting, measuring the displacement value, and obtaining the peroxynitrite ion concentration by comparing the linear equation; the fluorescent carbon quantum dots A are prepared by crocin T hydrothermal method; the fluorescent carbon quantum dots B are prepared by pyronine Y hydrothermal method. The present invention constructs a wavelength-shift-type sensing system for detecting peroxynitrite ions, which can realize the selective detection of peroxynitrite ions and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of substance detection, and in particular to a fluorescence detection method for peroxynitrite ions and application thereof. Background Art

[0002] Peroxynitrite ions are rapidly generated by the interaction between nitric oxide and superoxide anion free radicals. They are a type of reactive oxygen with strong oxidizing and nitrifying properties, which maintain the balance of the life system within a certain concentration range. However, high concentrations of peroxynitrite ions will inhibit the activity of antioxidant enzymes in cells, causing a weakening of the antioxidant capacity of cells, damaging cell function, affecting cell signal transduction, and even leading to adverse reactions such as cell membrane damage, DNA damage, protein inactivation, and cell apoptosis. Studies have shown that peroxynitrite ions are a representative early diagnostic marker for cardiovascular diseases and neurodegenerative diseases, with the characteristics of high activity and short half-life.

[0003] At present, researchers have reported a variety of methods for quantitative detection of peroxynitrite ions, mainly chemiluminescence, UV-visible absorption spectroscopy, electrochemical analysis and fluorescence analysis. However, most of these methods have disadvantages such as complex synthesis process, cumbersome labeling process, high cost and complex instrument operation, which limits their wide application in practical detection. In recent years, fluorescence detection method has attracted more and more attention due to its convenience, high sensitivity and low cost.

[0004] Although some progress has been made in the fluorescence detection of peroxynitrite ions in recent years, there are still challenges: (1) The change of single-wavelength fluorescence intensity is easily interfered by some accidental factors, such as instrument fluctuations and ambient temperature; (2) Traditional organic fluorescent probes usually have problems such as poor water solubility and poor resistance to photobleaching. Therefore, in order to solve the above problems, it is of great significance to develop a new peroxynitrite ion probe with high sensitivity, good selectivity and good stability. Summary of the invention

[0005] In order to overcome the problems existing in the existing fluorescence detection method of peroxynitrite ions, the present invention proposes a method for detecting peroxynitrite ions using carbon quantum dot composite nanomaterials. The detection method has low cost and simple operation, can detect peroxynitrite ions simply, quickly, efficiently and sensitively, and is not easily affected by factors such as environmental fluctuations.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for detecting peroxynitrite ions using a nanocomposite material comprises the following steps:

[0008] (1) mixing peroxynitrite ion standard samples of different concentrations with a carbon quantum dot nanocomposite solution, then exciting the samples at different concentrations, measuring the shift value of the emission peak at 495 nm, and obtaining a linear equation between the peroxynitrite ion concentration and the wavelength shift value;

[0009] (2) mixing the peroxynitrite ion sample to be measured with the carbon quantum dot nanocomposite solution, exciting the mixture, measuring the displacement value of the emission peak at 495 nm, and obtaining the peroxynitrite ion concentration according to the linear equation;

[0010] The carbon quantum dot nanocomposite material solution contains fluorescent carbon quantum dots A and fluorescent carbon quantum dots B; the fluorescent carbon quantum dots A are prepared from crocin T by a hydrothermal method; and the fluorescent carbon quantum dots B are prepared from pyronine Y by a hydrothermal method.

[0011] In the present invention, the carbon quantum dot nanocomposite material is a wavelength-shifted fluorescent probe comprising dual emission, one of which emits green fluorescence at 495nm; the other emits orange fluorescence at 570nm. Peroxynitrite ions can react with carbon quantum dots, resulting in the shift of the fluorescence emission peak. The content of peroxynitrite ions in the sample can be detected by the displacement value of the emission peak of the carbon quantum dots at 495nm. The detection system has high selectivity for peroxynitrite ions and can avoid interference with the accuracy and stability of the detection results caused by other external environments, instrument fluctuations and other factors.

[0012] Preferably, the preparation method of the fluorescent carbon quantum dots A comprises the following steps: crocin T is dissolved in water and subjected to a hydrothermal reaction at 180-220°C for 5-7 hours to obtain orange fluorescent carbon quantum dots A; further preferably, crocin T is dissolved in water and subjected to a hydrothermal reaction at 200°C for 6 hours to obtain orange fluorescent carbon quantum dots A.

[0013] Preferably, the preparation method of the fluorescent carbon quantum dots B comprises the following steps: pyronin Y is dissolved in water and subjected to a hydrothermal reaction at 160-200°C for 11-13 hours to obtain green fluorescent carbon quantum dots B; further preferably, pyronin Y is dissolved in water and subjected to a hydrothermal reaction at 180°C for 12 hours to obtain green fluorescent carbon quantum dots B.

[0014] In some preferred embodiments of the present invention, the preparation process of the fluorescent carbon quantum dots A and the fluorescent carbon quantum dots B further comprises the step of purifying the products after the reaction; preferably, the purification is carried out by dialysis and membrane filtration; further preferably, the dialysis is carried out by ultrapure water dialysis, and the membrane filtration is carried out by a 0.22 μm aqueous cellulose acetate membrane.

[0015] In the present invention, after crocin T reacts at 200° C. for 6 hours, the product emits orange fluorescence; after pyronin Y reacts at 180° C. for 12 hours, the product emits green fluorescence, and the fluorescence properties of the two are not affected after simple mixing.

[0016] Preferably, the carbon quantum dot nanocomposite material solution further comprises a phosphate buffer solution with a pH value of 3 to 11.

[0017] In some preferred embodiments of the present invention, the pH value of the carbon quantum dot nanocomposite solution is 7.4.

[0018] Preferably, the concentration of fluorescent carbon quantum dots A in the carbon quantum dot nanocomposite solution is 50-70 mg·mL -1 The concentration of fluorescent carbon quantum dots B in the carbon quantum dot nanocomposite solution is 40 to 60 μg mL -1 ; Further preferably, the concentration of fluorescent carbon quantum dots A in the carbon quantum dot nanocomposite solution is 55 to 65 mg·mL -1 The concentration of fluorescent carbon quantum dots B in the carbon quantum dot nanocomposite solution is 45-55 μg·mL -1 ; Further preferably, the concentration of fluorescent carbon quantum dots A in the carbon quantum dot nanocomposite solution is 60 mg·mL -1 ; The concentration of fluorescent carbon quantum dots B in the carbon quantum dot nanocomposite solution is 50 μg·mL -1 .

[0019] Preferably, the volume ratio of the peroxynitrite ion sample to be tested to the carbon quantum dot nanocomposite material solution is (0.01-25):1.

[0020] Preferably, the excitation wavelength is 300 nm to 410 nm; further preferably, the excitation wavelength is 410 nm.

[0021] Preferably, the concentration of the peroxynitrite ion sample to be measured is 0-3 μM, and the corresponding fluorescence wavelength shift range is 495.4 nm-478.7 nm.

[0022] The second aspect of the present invention provides the application of the method for detecting peroxynitrite ions using the nanocomposite material in fluorescence detection of peroxynitrite ions.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention uses carbon quantum dot nanocomposite materials as fluorescent probes for sensing and detecting peroxynitrite ions, and detects the displacement value of the emission peak at 495 nm, thereby constructing a wavelength-shifted sensing system for detecting peroxynitrite ions. The detection method can achieve selective detection of peroxynitrite ions and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a fluorescence emission spectrum of the carbon quantum dot nanocomposite material of Example 1 of the present invention under 410nm fluorescence excitation;

[0026] Figure 2 The fluorescence spectra of the carbon quantum dot nanocomposite material at 425nm to 650nm in different concentrations of peroxynitrite ions in Example 2 of the present invention are as follows;

[0027] Figure 3 The photos are of the carbon quantum dot nanocomposite material of the present invention before (left) and after (right) adding peroxynitrite ions under 365nm ultraviolet light irradiation;

[0028] Figure 4 Transmission electron microscope images of the carbon quantum dot nanocomposite material used in the present invention before (left) and after (right) the addition of peroxynitrite ions;

[0029] Figure 5 The standard working curve of the wavelength shift value of the detection system of Example 2 of the present invention to the peroxynitrite ion;

[0030] Figure 6 The working curve of the fluorescence intensity ratio and peroxynitrite ion of the detection system of Example 3 of the present invention;

[0031] Figure 7 This is the selective detection result of peroxynitrite ion by the detection system of Example 4 of the present invention. DETAILED DESCRIPTION

[0032] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0033] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0034] Example 1

[0035] This example prepares a carbon quantum dot nanocomposite solution, and the specific process is as follows:

[0036] 0.125g of crocin T was dissolved in 10mL of ultrapure water, then transferred to a reactor, heated at 200℃ for 6h, cooled to room temperature, and the obtained pink solution was further purified by dialysis with ultrapure water, and then filtered through a 0.22μm aqueous cellulose acetate membrane to remove large particles to obtain a carbon quantum dot nanomaterial solution, recorded as solution 1. 1mg of pyronine Y was dissolved in 10mL of ultrapure water, then transferred to a reactor, heated at 180℃ for 12h, cooled to room temperature, and the obtained pink solution was further purified by dialysis with ultrapure water, and then filtered through a 0.22μm aqueous cellulose acetate membrane to remove large particles to obtain a carbon quantum dot nanomaterial solution, recorded as solution 2. The two were simply mixed to obtain a carbon quantum dot nanocomposite solution, recorded as solution 3. It was observed that solution 1 emitted orange fluorescence, solution 2 emitted green fluorescence, and solution 3 emitted orange-yellow fluorescence. The excitation wavelength was set to 410nm, and the carbon quantum dot nanocomposite had obvious absorption peaks at 495nm and 570nm, such as Figure 1 shown.

[0037] The carbon quantum dot nanocomposite solution and the carbon quantum dot nanocomposite solution containing 250 μM peroxynitrite ions were irradiated under ultraviolet light. Figure 3 As shown; and observed both under a transmission electron microscope, the results are as follows Figure 4 As shown. Figure 3 It can be seen that after peroxynitrite ions are added to the carbon quantum dot nanocomposite solution, the fluorescence of the solution changes from orange-yellow to green.

[0038] Example 2

[0039] This example establishes a standard method for detecting peroxynitrite ions using a wavelength shift method, and the specific process is as follows:

[0040] Take 800 μL of peroxynitrite ion solution of different concentrations (0-3 μM) and 100 μL of carbon quantum dot nanocomposite solution (concentration of 100 μg / mL) and 100 μL of buffer solution (pH = 7.4, 10 mM) respectively, the total volume of the solution is 1 mL, and mix them evenly. The excitation wavelength is set to 410 nm, and the fluorescence intensity of the system is measured at 425 nm to 650 nm. Figure 2 As shown, the wavelength shift value is statistically calculated.

[0041] like Figure 5 As shown, there is a quantitative relationship between the wavelength shift value and the peroxynitrite ion concentration. The linear equation of the working curve in the peroxynitrite ion concentration range of 0 to 3 μM is Δ λ =5.75x+0.121,R2 =0.996, and the detection limit is 0.49 μM.

[0042] Example 3

[0043] This example verifies the standard method for detecting peroxynitrite ions proposed in Example 2, and the specific process is as follows:

[0044] Take 800 μL of peroxynitrite ion solution of different concentrations (0-3 μM) and 100 μL of carbon quantum dot nanocomposite solution (concentration of 100 μg / mL) and 100 μL of buffer solution (pH = 7.4, 10 mM) respectively, the total volume of the solution is 1 mL, and mix them evenly. The excitation wavelength is set to 410 nm, and the fluorescence intensity of the system is measured at 425 nm to 650 nm. Figure 2 The fluorescence intensity ratio of the two was calculated.

[0045] like Figure 6 As shown in Figure 2, there is a quantitative relationship between the fluorescence intensity ratio and the peroxynitrite ion concentration. The linear equation of the working curve in the peroxynitrite ion concentration range of 0 to 3 μM is F 570 / F p =-0.122x+1.73,R 2 =0.996.

[0046] Example 4

[0047] This example performs a selective test for peroxynitrite ion detection, and the specific process is as follows:

[0048] Different interfering substances were selected, including hydroxyl radical, singlet oxygen, hydrogen peroxide, peroxyl radical, nitrite ion, fluoride ion, chloride ion, bromide ion, iodide ion, sulfide ion, thiocyanate ion, bicarbonate ion, oxalate ion, dihydrogen phosphate ion, potassium ion, sodium ion, copper ion, iron ion, calcium ion, magnesium ion, manganese ion, chromium ion, sodium azide, glucose, glutathione, ascorbic acid, glycine, aspartic acid, cysteine, tyrosine, phenylalanine, arginine, isoleucine, valine, leucine, histidine, alanine, threonine, methionine, proline, and glutamic acid. The concentrations of peroxynitrite ion and interfering substances were all 250 μM. The test results are as follows: Figure 7 As shown, it can be found that the above interferences have little effect on the wavelength shift value of the carbon quantum dot nanocomposite solution, indicating that the peroxynitrite ion detection method has good selectivity.

[0049] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A method for detecting peroxynitrite ions using a nanocomposite material, characterized in that: The following steps are involved: (1) mixing peroxynitrite ion standard samples of different concentrations with a carbon quantum dot nanocomposite solution, then exciting the samples at different concentrations, wherein the excitation wavelength is 300 nm to 410 nm, measuring the shift value of the emission peak at 495 nm, and obtaining a linear equation between the peroxynitrite ion concentration and the wavelength shift value; (2) Mixing the peroxynitrite ion sample to be tested with the carbon quantum dot nanocomposite solution for excitation, wherein the excitation wavelength is 300nm to 410nm, measuring the displacement value of the emission peak at 495nm, and obtaining the peroxynitrite ion concentration according to the linear equation; the carbon quantum dot nanocomposite solution contains fluorescent carbon quantum dots A and fluorescent carbon quantum dots B; the fluorescent carbon quantum dots A are prepared from crocin T by a hydrothermal method; the fluorescent carbon quantum dots B are prepared from pyronine Y by a hydrothermal method; the preparation method of the fluorescent carbon quantum dots A comprises the following steps: crocin T is dissolved in water and subjected to a hydrothermal reaction at 180 to 220°C for 5 to 7h to obtain orange fluorescent carbon quantum dots A; the preparation method of the fluorescent carbon quantum dots B comprises the following steps: pyronine Y is dissolved in water and subjected to a hydrothermal reaction at 160 to 200°C for 11 to 13h to obtain green fluorescent carbon quantum dots B.

2. The method for detecting peroxynitrite ions using a nanocomposite material according to claim 1, wherein: The carbon quantum dot nanocomposite material solution also includes a phosphate buffer solution with a pH value of 3-11.

3. The method for detecting peroxynitrite ions using a nanocomposite material according to claim 1, wherein: The concentration of the fluorescent carbon quantum dots A in the carbon quantum dot nanocomposite solution is 50 to 70 mg·mL -1 The concentration of fluorescent carbon quantum dots B in the carbon quantum dot nanocomposite solution is 40 to 60 μg mL -1 .

4. The method for detecting peroxynitrite ions using a nanocomposite material according to claim 1, wherein: The volume ratio of the peroxynitrite ion sample to be tested to the carbon quantum dot nanocomposite material solution is (0.01-25):

1.

5. The method for detecting peroxynitrite ions using a nanocomposite material according to claim 1, characterized in that: The excitation wavelength is 410 nm.

6. The method for detecting peroxynitrite ions using a nanocomposite material according to claim 1, characterized in that: The concentration of the peroxynitrite ion sample to be tested is 0-3 μM, and the corresponding fluorescence wavelength shift range is 495.4 nm-478.7 nm.

7. Use of the method for detecting peroxynitrite ions using the nanocomposite material according to any one of claims 1 to 6 in fluorescence detection of peroxynitrite ions.

Citation Information

Patent Citations

  • Fluorescent probe for detecting peroxynitrite ions, preparation method and applications thereof

    CN110964022A

  • Orange fluorescent carbon dot and application thereof in detection of peroxynitrite ions

    CN111647401A